PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN KEKERASAN SEKSUAL DITINJAU DARI SISI KEMANFAATAN BAGI KORBAN - Anggreany Haryani Putri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
As the future generation of the nation, children must grow up in a safe and protected environment. However, in reality, children remain vulnerable to sexual crimes, which have severe physical and psychological impacts. Legal protection for child victims of sexual crimes is regulated under various laws, but the implementation is still far from optimal. A justice system that focuses more on perpetrators and the lack of adequate compensation for victims are among the main challenges. This research formulates two main issues: first, how is the legal protection for children as victims of sexual crimes regulated? Second, how is the sentencing of perpetrators of child sexual abuse viewed from the perspective of legal benefit? The type of research used is normative juridical. The findings indicate that efforts to restore the psychological condition of child victims — such as counseling, support, and therapy — must be optimized. Thus, sentencing should not only focus on punishment but also consider the physical and psychological condition of the child as the victim. Therefore, perpetrators should be subject to additional penalties, such as restitution, as a deterrent.